2019
DOI: 10.1097/iae.0000000000002206
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Shape-Descriptive Factors for the Progression of Geographic Atrophy Secondary to Age-Related Macular Degeneration

Abstract: These findings confirm the relevance of shape-descriptive factors and previous progression as prognostic variables for geographic atrophy progression. However, a substantial part of the remaining variation in geographic atrophy progression seems to depend on other variables, some of which are visible in optical coherence tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 67 publications
4
59
0
Order By: Relevance
“…4 Some authors found advantageous the square-root transformation of the RPE-atrophy rates because it may reduce the effect of baseline RPEatrophy area. 4,[50][51][52] In our study, we repeated all the analyses with the square-root-transformed RPEatrophy progression rate as the dependent variable, and we found similar results to nontransformed data.…”
Section: Discussionsupporting
confidence: 54%
“…4 Some authors found advantageous the square-root transformation of the RPE-atrophy rates because it may reduce the effect of baseline RPEatrophy area. 4,[50][51][52] In our study, we repeated all the analyses with the square-root-transformed RPEatrophy progression rate as the dependent variable, and we found similar results to nontransformed data.…”
Section: Discussionsupporting
confidence: 54%
“…Patients were recruited in the context of the noninterventional prospective natural history study Directional Spread in Geographic Atrophy (DSGA, NCT02051998) at the Department of Ophthalmology at the University Hospital in Bonn, Germany. 19,20 Briefly, patients had to be at least 55 years of age and exhibit unifocal or multifocal GA, defined as any sharply demarcated round or oval-shaped lesion of at least 0.05 mm 2 in area, and have clearly reduced FAF in the context of AMDassociated changes (i.e., drusen and pigment abnormalities). 19 Exclusion criteria included the presence of other retinal diseases such as diabetic retinopathy or retinal dystrophy, as well as a history of laser photocoagulation or retinal surgery, any signs of active or regressed exudation (e.g., hemorrhages, exudates, fibrous scarring), as well as refractive errors >5.00 diopters spherical equivalent or >2.50 diopters astigmatism in the study eye.…”
Section: Methods Patientsmentioning
confidence: 99%
“…Of the 27 publications found, 18 were dedicated to GA segmentation only (e.g. lesions or retinal layers that explain GA), 2 focused on the detection and classification of GA, 2 assessed overall GA progression (with one including segmentation as well), 3 assessed spatial GA progression (with 2 including segmentation), and finally 2 assessed visual function prediction in GA. No publications were found that discussed other aspects of automating GA, such as the automated extraction of hyperfluorescent areas, although some, such as Pfau et al, 43 did assess hyperfluorescent phenotypes in the modeling process. Sample sizes ranged from 16 to 59,812 images with the latter being a subset of images from the Age-Related Eye Disease Study (AREDS) dataset and used by Keenan et al (2019) 24 for the detection and classification of GA-related models.…”
Section: Resultsmentioning
confidence: 99%
“…Two publications discussed overall GA progression: Pfau et al and Liefers et al 43 , 44 Pfau and colleagues evaluated shape-descriptive factors on lesion progression and they quantified this using a linear mixed-effects model with a two-level random effect (i.e. eye- and patient-specific effects).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation